The IMPLEMENTATION OF PRODUCTION STAGES IN THE RADIO FEATURE PROGRAM “Suara Dari Tanah Jauh” - Ismed, Mohammad; Kayla Maisie Ayu Putri Muslim (Jurnal Ilmiah Publipreneur, 2025)
In order to create the radio feature program "Suara dari Tanah Jauh," this study examines the critical role that the producer plays in putting methodical production phases into place. The show tells the stories of Indonesian students who study overseas and how they adjust to different cultural settings. Data were gathered through literature research, online questionnaires using Google Forms, and listening to similar radio shows using a qualitative descriptive methodology. According to the study, the producer serves as the primary coordinator, making ensuring that all phases—from pre-production to production to post-production—run smoothly and in unison. To create an educational, poignant, and creative broadcast, the producer combines conceptual, artistic, technical, and management components. Additionally, it was discovered that the methodical use of production stages improved overall, maximized scheduling and budgeting, and fostered creative collaboration.